Integrating Artificial Intelligence in Healthcare : Improving Patient Care and Diagnosis - Taye Bekele; Haile Mekonnen (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2022)
Artificial intelligence (AI) has shown great potential in revolutionizing the healthcare sector by enhancing diagnosis accuracy and optimizing treatment plans. This paper investigates the application of AI technologies in healthcare, focusing on machine learning algorithms, natural language processing, and predictive analytics. The study evaluates several case studies where AI has been implemented to assist in early disease detection, personalized treatment, and patient management. Results suggest that AI integration leads to improved healthcare outcomes and efficiency, transforming patient care practices.